General and math vocabulary contributions to early numeracy skills in a large population-representative sample - Bleses, Dorthe; Moos, Martin; Purpura, David J.; Dale, Philip S. (Frontiers in Developmental Psychology, 2023)
There are well-documented associations between numeracy development in preschool age children and general and math vocabulary, literacy, and executive functions., However, the studies have largely included small samples of children with parents with either predominantly low or higher socioeconomic background (SES); further, few studies have included measures of all these domains in the same analyses. In this current study, we examined how general vocabulary, math vocabulary, rhyme detection and three measures of executive functions are associated with numeracy development in a population representative sample of 2931 Danish children 3-5 years (51% male, 89% white). Multi-level regressions controlling for child age and, sex, and in some analyses also parental education and income confirmed that general vocabulary (β=0.16), math language (β=0.17), rhyme detection (β=0.14), attention shifting (β=0.09), inhibitory control (β=0.05), and working memory (β=0.09) each are associated with numeracy after controlling for covariates when estimated in the same model. Analyses of extreme performance (low-high) suggests a much closer and symmetrical connection between math language and numeracy compared to that between general vocabulary and numeracy. Interestingly, family SES is weakly but significantly related to all measures, most strongly for the vocabulary measures, but does not influence the pattern of results from regression analyses. In conclusion, both general vocabulary and mathematics-specific vocabulary contribute substantially to early numeracy skills. Rhyme detection and executive functions are also associated with numeracy skills, but with a lower magnitude.